Religious Phenomena in the Digital World: Expressions and Narratives of Moderation on the Website tanwir.ID - Achmad Syariful Afif; Dhur Anni; Muhammad Yuchbibun Nury (Jurnal Studi Agama, 2024)
Exponential technological developments are driving the transformation of society to the digital world. Data published by domo.com shows 6.3 million searches occur on Google every minute in 2023. Realizing the importance of adaptation in the digital world for da'wah and religious propagation, the Islamic world began to develop various social media channels, applications and websites. Moreover, content and narratives exposed to extreme thinking are also amplified by this technological sophistication, this adds to the urgency of the presence of moderation content as a counter-narrative to this reality. This research takes the tanwir.ID website as the object of research, a website that is quite prominent and managed by Muhammadiyah, which is one of the largest Islamic organizations in Indonesia. The homepage compiled by tanwir.ID consists of Tafsir, Ulumul Qur'an, Insight, Indept and Video. However, in this study the author limits it to posts that discuss moderation in religion and related to it. The analysis technique was carried out by collecting research data through articles written on the tanwir.ID website since its inception, until posts in June 2024. The purposive sampling technique was used to sort out articles relevant to the theme of moderation. This data was then analyzed using narrative analysis techniques to identify the main themes and strategies for conveying ideas. The results of this study show that tanwir.id contributes to narrating moderate attitudes in religion through the articles it publishes through various narrative strategies, such as book reviews, interactive discussions, religious text-based arguments (tafsir), and contextualization of religious texts with current phenomena. Published articles often emphasize the importance of reconciliation (peace) both intra and inter-religious, fair and proportional attitudes, and avoiding extreme, fanatical and exclusive attitudes.